Hospitalizations due to road traffic crashes involving motorcycles - Azevedo, Ulicélia Nascimento (2017)
Objective: To analyze hospitalizations due to road traffic crashes involving motorcycles. Methods: A descriptive study of SUS-funded hospitalizations due to road traffic crashes (RTC) involving motorcycles in people living in the State of Rio Grande do Norte, Brazil, from 2008 to 2016. Data were obtained from the Hospital Information System of the Unified Health System (SIH/SUS). Hospitalization rates were stratified by gender, age group and health region. The proportion of hospitalization costs was also analyzed. Results: There were 15,233 RTC involving motorcyclists in the period analyzed, with a hospitalization coefficient of 4.38/1000 inhabitants. The hospitalization coefficient was higher among men (6:1). The most prevalent age groups were 20-34 years and over 70 years. The Metropolitan Region recorded the highest number of hospitalizations due to motorcycle accidents (n= 4,260), but the Santa Cruz Region presented the highest proportion of motorcycle accidents in relation to the RTC (75%). The State Government spent R$ 17,916,327.90 on hospitalizations due to these accidents, which represents 66.16% of RTC expenses. Conclusion: There was a high proportion of hospitalizations due to motorcycle crashes in the state of Rio Grande do Norte in relation to road traffic crashes. The crashes involved mostly young men, with increased expenses due to these hospitalizations.